2023
DOI: 10.1007/s10344-023-01732-9
|View full text |Cite
|
Sign up to set email alerts
|

Wild boar (Sus scrofa) as a potential reservoir of infectious agents in Portugal: a review of two decades (2001–2021)

Catarina Jota Baptista,
Fernanda Seixas,
José M. Gonzalo-Orden
et al.

Abstract: The wild boar (Sus scrofa) is a mammal with a broad distribution in the Eurasian territory and a potential reservoir for several zoonotic pathogens. Besides being part of the Mediterranean ecosystem and perpetuating these agents in the environment, this species is usually consumed in the Iberian Peninsula, representing a potential public health threat. Due to its extensive expansion and colonization of new geographical areas, which leads to increasing contact with humans, domestic animals, and wildlife, infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…[ 67 ]. Wild ungulates are regarded as a reservoir of various infectious illnesses in the Iberian Peninsula, including tuberculosis, brucellosis, and paratuberculosis [ 68 , 69 , 70 ]. Wildlife interacts with humans, domestic cattle, and pet animals and so can serve as reservoirs and sources of infection and zoonotic diseases spread to the human interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…[ 67 ]. Wild ungulates are regarded as a reservoir of various infectious illnesses in the Iberian Peninsula, including tuberculosis, brucellosis, and paratuberculosis [ 68 , 69 , 70 ]. Wildlife interacts with humans, domestic cattle, and pet animals and so can serve as reservoirs and sources of infection and zoonotic diseases spread to the human interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…This expansion has led to various implications, especially concerning infectious diseases and zoonotic risks associated with wild boar. Studies have identified wild boar as potential reservoirs for infectious agents like HEV, Coxiella, and Brucella [18]. The presence of these pathogens in wild boar poses risks not only to wildlife but also to domestic animals and humans due to potential zoonotic transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The adaptability of wild boar to different habitats and food resources contributes to their continuous occupation of new geographic regions, further necessitating comprehensive infectious disease assessments. It is crucial to understand the prevalence of pathogens in wild boar for infectious disease surveillance, disease management strategies, and wildlife conservation efforts in Portugal [18].…”
Section: Introductionmentioning
confidence: 99%
“…This expansion has led to various implications, especially concerning infectious diseases and zoonotic risks associated with wild boar. Studies have identified wild boar as potential reservoirs for infectious agents like HEV, Coxiella and Brucella [19][20][21]. The presence of these pathogens in wild boar poses risks not only to wildlife but also to domestic animals and humans due to potential zoonotic transmission.…”
Section: Introductionmentioning
confidence: 99%